Exergaming for Quality of Life in Persons Living with Chronic Diseases: A Systematic Review and Meta‐analysis. Issue 7 (10th September 2020) - Cugusi, Lucia; Prosperini, Luca; Mura, Gioia
Abstract : Objective: To evaluate the evidence of effectiveness of exergame‐based rehabilitative interventions on health‐related quality of life (HRQoL) in persons with chronic diseases. Type: Systematic review and meta‐analysis. Literature survey: Randomized and nonrandomized controlled trials of exergame rehabilitation interventions in populations with chronic diseases reporting HRQoL outcomes were identified by searching PubMed, Scopus, Physiotherapy Evidence Database (PEDro), Cochrane Central Register of Controlled Trials (CENTRAL), and Google Scholar, using keywords and MeSH terms for papers published between January 2005 and March 2019. Methodology: Risk of bias was assessed by using the PEDro scale. The Grading of Recommendation, Assessment, Development and Evaluation (GRADE) system was used to score the quality of evidence. Pooled effects were reported as standardized mean differences (SMDs) or weighted mean difference (MDs) and 95% confidence intervals (CIs), using a random‐effects model. Heterogeneity was weighted by inconsistency I 2 tests. Synthesis: Thirty‐four trials were identified (1594 participants). Overall, the evidence was low quality. Exergames significantly improved HRQoL in populations with chronic diseases, with a small effect size (32 studies; 1544 participants; SMD 0.24; 95% CI 0.1 to 0.4; I 2  = 27%) and specifically in people with neurological disorders (20 studies, 956 participants, SMD 0.22; 95% CI 0.2 to 0.4; I 2  = 49%), rheumatologic diseases (four studies, 210 participants, SMD 0.39; 95% CI 0.1 to 0.7; I 2  = 4%), and cardiorespiratory and chronic metabolic conditions (five studies, 309 participants, SMD 0.23; 95% CI 0.0 to 0.5; I 2  = 0%). Exergaming interventions in health care settings demonstrated similarly small but positive effects (22 studies, 905 participants, SMD 0.30; 95% CI 0.1 to 0.5; I 2  = 41%), whereas those carried out in home‐based contexts did not. Conclusions: Exergame‐based rehabilitative interventions performed in health care settings led to small but statistically significant improvements in HRQoL in persons with chronic diseases.